Deconstructing and reconstructing cross-language transfer in bilingual reading development: An interactive framework - Chung, Sheila Cira; Chen, Xi; Geva, Esther (Journal of neurolinguistics, 2019)
The concept of cross-language transfer is central in bilingual reading development. This is because researchers and educators search for the conditions that allow learning that takes place in one language to enhance learning in the other language (Perkins & Salomon, 1992). In the past, the research focus was primarily on cross-language transfer in spoken language. However, since the 90s, cross-language transfer has been studied in relation to literacy aspects, such as word reading, spelling, reading comprehension, and writing. One can find several useful cross-language transfer frameworks in the literature: the contrastive-typological framework (Lado, 1964), the linguistic interdependence framework (Cummins, 1981), the common underlying cognitive process (Geva & Ryan, 1993), and the transfer facilitation model (Koda, 2008). Many studies on L2 transfer have been situated in one of these frameworks, though some treat them as complementary in nature. In what follows, we first briefly describe the core characteristics of each framework. We then present a systematic review of the empirical studies that have been conducted to examine cross-language transfer. Finally, based on the available theoretical and empirical evidence, we propose an interactive framework in an attempt to capture the complex linguistic and cognitive processes involved in cross-language transfer. •Cross-language transfer is influenced by linguistic and cognitive factors.•Transfer of certain construct may be the result of the interaction of multiple factors.•It is difficult to make predictions of the direction and extent of transfer for any given construct.